STEREOTYPES AND PERCEPTIONS IN SOCIETY OF THE ELDERLY AS A SYMPTOM OF CULTURAL DIFFERENCES IN EUROPEAN, ASIAN AND AMERICAN COUNTRIES - Grabowska, Beata (Acta Universitatis Nicolai Copernici. Zarządzanie, 2020)
At the turn of the twentieth and twenty-first centuries, there were significant changes in the age structure of society, although they show different intensity in different regions of the world. The effects of the global aging of the population and its regional diversification imply new phenomena and problems, not only demographic, but most of all economic, political, cultural, mental and social [Abramski, 2017]. The cult of youth is promoted in aging societies, in which a larger group of people 50+ participates, and the dominance of values characteristic of this period is becoming more and more a source of stereotypes and discrimination against the elderly [Mizińska, 2008]. The differences in the perception of people aged 50+ result from the different cultures prevailing in these countries. The aim of the work is to systematize knowledge about the stereotype of a mature and elderly person and to show cultural differences in the perception of older people in European, Asian and American countries.